The dark side of foetal bovine serum in extracellular vesicle studies - Ornella Urzì; Roger Olofsson Bagge; Rossella Crescitelli (Journal of Extracellular Vesicles, 2022)
Abstract Extracellular vesicles (EVs) have been shown to be involved in cell‐cell communication and to take part in both physiological and pathological processes. Thanks to their exclusive cargo, which includes proteins, lipids, and nucleic acids from the originating cells, they are gaining interest as potential biomarkers of disease. In recent years, their appealing features have been fascinating researchers from all over the world, thus increasing the number of in vitro studies focused on EV release, content, and biological activities. Cultured cell lines are the most‐used source of EVs; however, the EVs released in cell cultures are influenced by the cell culture conditions, such as the use of foetal bovine serum (FBS). FBS is the most common supplement for cell culture media, but it is also a source of contaminants, such as exogenous bovine EVs, RNA, and protein aggregates, that can contaminate the cell‐derived EVs and influence their cargo composition. The presence of FBS contaminants in cell‐derived EV samples is a well‐known issue that limits the clinical applications of EVs, thus increasing the need for standardization. In this review, we will discuss the pros and cons of using FBS in cell cultures as a source of EVs, as well as the protocols used to remove contaminants from FBS.